Mortgage choice and expenditure over the lifecycle: Evidence from expiring interest-only loans - Henrik Yde Andersen; Stine Ludvig Bech (Danmarks Nationalbank, 2020)
We study how homeowners' consumption responds to a negative and anticipated disposable income shock: the beginning of the amortisation period on interest-only mortgages. We identify spending behavior through an event study approach, by matching loan-level data that covers the universe of Danish mortgages to detailed administrative registries on borrowers. In response to an average increase in installments worth 9 percent of income, consumption drops by 3 percent of income, in the year when amortisation begins. The reduction in expenditure is persistent. Borrowers who fail to smooth consumption are highly leveraged, handto- mouth consumers, likely to be unable to obtain a new interest-only loan.
Keywords: D15; E21; G51; 330; Interest-only; Mortgages; Consumption